Pegylation Reduces the Uptake of Certolizumab Pegol by Dendritic Cells and Epitope Presentation to T-Cells - de Bourayne, Marie; Meunier, Sylvain; Bitoun, Samuel; Correia, Evelyne; Mariette, Xavier; Nozach, Hervé; Maillère, Bernard (Frontiers in Immunology, 2022)
Pegylation of biopharmaceuticals is the most common strategy to increase their half-life in the blood and is associated with a reduced immunogenicity. As antigen presentation is a primary event in the activation of CD4 T-cells and initiation of Anti-Drug Antibody (ADA) response, we investigated the role of the PEG molecule on the T-cell reactivity of certolizumab pegol (CZP), a pegylated anti-TNFα Fab. We generated T-cell lines raised against CZP and its non-pegylated form (CZNP) and demonstrated CZP primed few T-cells in comparison to CZNP. CZP-primed lines from 3 donors responded to a total of 5 epitopes, while CZNP-primed lines from 3 donors responded to a total of 7 epitopes, 4 epitopes were recognized by both CZP- and CZNP-primed lines. In line with this difference of T-cell reactivity, CZP is less internalized by the dendritic cells than CZNP. In vitro digestion assay of CZP by Cathepsin B showed a rapid removal of the PEG moiety, suggesting a limited influence of PEG on CZP proteolysis. We therefore demonstrate that pegylation diminishes antigen capture by dendritic cells, peptide presentation to T-cells and T-cell priming. This mechanism might reduce immunogenicity and contribute to the long half-life of CZP and possibly of other pegylated molecules.